Glutamate-Dependent Activation of NF-κB During Mouse Cerebellum Development - Guerrini, Luisa (J Neurosci, 1997)
NF-κB and activator protein 1 (AP-1) are dimeric transcription factors involved in transcriptional regulation in many cells, including neurons. We have examined their activity during mouse cerebellum development, a postnatal process starting just after birth and completed by the fourth postnatal (PN) week. The activity of these factors was analyzed by binding of nuclear extracts to a synthetic oligonucleotide representing the κB site of human immunodeficiency virus or the AP-1 site of the urokinase promoter. NF-κB activity was observed from 7 PN, was restricted to the developing cerebellum, and was not observed in the early postnatal neocortex and hippocampus. On the other hand, AP-1 activity was not found in cerebellum but was present in both neocortex and hippocampus. Moreover, a κB-driven transgene was found to be increasingly expressed in the cerebellum from 5 PN to 10 PN but not in the adult. The regulation of NF-κB activation in mouse cerebellum was analyzed by intraperitoneal injection of glutamate receptor antagonists to 9 PN mice, which abolished NF-κB-binding activity, suggesting an endogenous loop of glutamate receptor activation. Glutamate receptor agonists, on the other hand, induced NF-κB nuclear translocation in the cerebellum of 5 PN mice, which is a stage in which NF-κB is not yet endogenously activated. This effect was specific for NF-κB and not observed for AP-1. In adult mice, NF-κB activity was absent in the cerebellum and was not induced by intraperitoneal injection of glutamate receptor agonists. These data show that NF-κB is specifically activated during cerebellum development and indicate an important role of glutamate receptors in this process.